A Computational Investigation of Cathinone, the Major Psychotropic Alkaloid from Muguka (a Cultivar of Catha edulis), Co-administered with Diazepam - Rajab, Mohamed Said (Sciences of Phytochemistry, 2026)
Muguka, a high-cathinone cultivar of Catha edulis consumed widely in East Africa, presents a growing health risk when co-administered with diazepam. This theoretical study represents one of the first integrated computational investigations focusing on the interaction between Muguka derived cathinone and diazepam, combining molecular docking, ADMET profiling, and physiologically based pharmacokinetic (PBPK) modeling. The in silico analysis identified overlapping CYP2D6 and CYP2C19 pathways, supporting potential mutual metabolic inhibition. The predictive PBPK models suggest moderate CYP2D6/CYP2C19-mediated drug-drug interactions based on a simulated oral dose of 100 mg cathinone and 30 mg diazepam in a human adult population. Co-administration is predicted to increase cathinone systemic exposure by 1.5-fold (AUC ↑50%) and reduce clearance by 33%, while diazepam exposure is projected to rise by 1.3-fold (AUC ↑30%) with 24% clearance reduction. Molecular docking revealed high-affinity binding of cathinone (-6.4 kcal/mol) at the dopamine transporter (DAT) and diazepam (-6.8 kcal/mol) at the γ-aminobutyric acid-A (GABA-A) receptor, indicating distinct yet potentially complementary CNS targets. Collectively, these computational predictions suggest that co-use may prolong CNS exposure and theoretically enhance neurotoxicity, and dependence risk. This integrated computational framework provides a hypothetical mechanistic evidence for stimulant-benzodiazepine interactions and underscores the need for clinical monitoring and validation.